Phenolic Compounds Isolated from Calea uniflora Less. Promote Anti-Inflammatory and Antioxidant Effects in Mice Neutrophils (Ex Vivo) and in Mice Pleurisy Model (In Vivo) - da Rosa, Julia Salvan; Nascimento, Marcus Vinicius Pereira Dos Santos; Parisotto, Eduardo Benedetti; Lima, Tamires Cardoso; Santin, José Roberto; Biavatti, Maique Weber; Zamoner, Ariane; Dalmarco, Eduardo Monguilhott; Fröde, Tânia Silvia (Mediators of Inflammation, 2019)
The literature shows that phenolic compounds possess important antioxidant and anti-inflammatory activities; however, the mechanism underlying these effects is not elucidated yet. The genus Calea is used in folk medicine to treat rheumatism, respiratory diseases, and digestive problems. In this context, some phenolic compounds were isolated with high purity from Calea uniflora Less. and identified as noreugenin (NRG) and α-hydroxy-butein (AH-BU). The aim of this study was to analyze the effect of these compounds on cell viability, the activity of myeloperoxidase (MPO), and apoptosis of mouse neutrophils using ex vivo tests. Furthermore, the effect of these compounds on the cytokines, interleukin 1 beta (IL-1β), interleukin 17A (IL-17A), and interleukin 10 (IL-10), and oxidative stress was investigated by analyzing lipid peroxidation (the concentration of thiobarbituric acid reactive substances (TBARS)) and activities of antioxidant enzymes, superoxide dismutase (SOD), catalase (CAT), and glutathione S-transferase (GST), using a murine model of neutrophilic inflammation. The NRG and AH-BU reduce MPO activity and increase neutrophil apoptosis (p<0.05). These compounds reduced the generation of oxygen reactive species and IL-1β and IL-17A levels but increased IL-10 levels (p<0.05). This study demonstrated that NRG and AH-BU show a significant anti-inflammatory effect by inhibiting the MPO activity and increasing neutrophil apoptosis in primary cultures of mouse neutrophils. These effects were at least partially associated with blocking reactive species generation, inhibiting IL-1β and IL-17A, and increasing IL-10 levels.